Going Solo : Doing Videojournalism in the 21st Century - Smith, G. Stuart (Book collections on Project MUSE., 2011)
Going Solo: Doing Videojournalism in the 21st Century details the controversy, history, and rise of this news genre, but its main objective is to show aspiring videojournalists how to learn the craft. While other textbooks depict the conventional reporter-and-videographer mode, Going Solo innovates by teaching readers how to successfully juggle the skill traditionally required of two different people.